HIV-1 Pr55Gag binds genomic and spliced RNAs with different affinity and stoichiometry. Issue 1 (2nd January 2017) - Bernacchi, Serena; Abd El-Wahab, Ekram W.; Dubois, Noé; Hijnen, Marcel; Smyth, Redmond P.; Mak, Johnson; Marquet, Roland; Paillart, Jean-Christophe
ABSTRACT: The HIV-1 Pr55 Gag precursor specifically selects genomic RNA (gRNA) from a large variety of cellular and spliced viral RNAs (svRNAs), however the molecular mechanisms of this selective recognition remains poorly understood. To gain better understanding of this process, we analyzed the interactions between Pr55 Gag and a large panel of viral RNA (vRNA) fragments encompassing the main packaging signal (Psi) and its flanking regions by fluorescence spectroscopy. We showed that the gRNA harbors a high affinity binding site which is absent from svRNA species, suggesting that this site might be crucial for selecting the HIV-1 genome. Our stoichiometry analysis of protein/RNA complexes revealed that few copies of Pr55 Gag specifically associate with the 5′ region of the gRNA. Besides, we found that gRNA dimerization significantly impacts Pr55 Gag binding, and we confirmed that the internal loop of stem-loop 1 (SL1) in Psi is crucial for specific interaction with Pr55 Gag . Our analysis of gRNA fragments of different length supports the existence of a long-range tertiary interaction involving sequences upstream and downstream of the Psi region. This long-range interaction might promote optimal exposure of SL1 for efficient Pr55 Gag recognition. Altogether, our results shed light on the molecular mechanisms allowing the specific selection of gRNA by Pr55 Gag among a variety of svRNAs, all harboring SL1 in their first common exon.